Watching sports and happiness among older adults in Japan: The JAGES cohort study - Kenjiro Kawaguchi; Kazushige Ide; Satoru Kanamori; Taishi Tsuji; Katsunori Kondo (PLoS ONE, 2025)
Objective While watching sports may enhance older adults’ happiness, the relationship between sports spectatorship and happiness may vary depending on on-site or TV/Internet. This study examined associations between different forms of sports spectatorship (on-site and TV/Internet) and happiness among older adults in Japan. Methods We used data from the Japan Gerontological Evaluation Study, conducted in 2019 and 2022. The outcome variable was happiness, and the explanatory variables were watching sports on-site, watching professional sports on-site, and watching sports on TV/Internet. Multiple linear regression was performed to examine the association between watching sports and happiness, after adjusting for potential confounders. A modified Poisson regression analysis was performed for the binarized outcome with a cutoff of 8 points. Subgroup analyses were conducted based on sports club participation, age, and sex. Results Watching sports on-site a few times annually was associated with higher happiness scores (B: 0.11, 95% CI: 0.03 to 0.19) and a higher prevalence of happiness (PR: 1.07, 95% CI: 1.03 to 1.12) than not watching sports. Similar results were observed when the participants watched professional sports a few times annually (B: 0.12, 95% CI: 0.02 to 0.22; PR: 1.06, 95% CI: 1.01 to 1.12). No significant associations were found between watching sports on TV/Internet and happiness. The associations were more pronounced among participants who did not participate in sports clubs, males, and those aged <  75 years. Conclusion Watching sports on-site, particularly a few times a year, was associated with higher happiness levels among older adults. These findings highlight the importance of developing targeted interventions that promote older adults’ access to live sports events as a public health strategy.